Awareness and Knowledge of Glaucoma and their Associated Factors among People Visiting a Tertiary Level Hospital in Central Nepal - Shrestha, A.; Shrestha, P.; Shrestha, T.; Shrestha, R. M.; Sujakhu, D.; Dhakal, K.; Thapa, G.; Adhikari, S.; Karki, S.; Adhikari, B. (Kathmandu University Medical Journal, 2022)
Background Glaucoma is one of the major causes of irreversible blindness globally. Almost 60 million people globally are affected by glaucoma making it the second leading cause of blindness worldwide. Diagnosis of glaucoma early on is vital for timely management and prevention of blindness. However, it is challenging to diagnose it early because it is asymptomatic in the initial stage, and there is also the dearth of appropriate screening tools. Awareness, knowledge, and beliefs are believed to influence the treatment-seeking behavior of people as well as their uptake of services. Objective To assess the awareness and knowledge about glaucoma among general patients and patient attendants visiting Dhulikhel Hospital. Method We conducted a cross sectional quantitative study among general patients visiting Dhulikhel Hospital. We collected data using face-to-face interviews with semi-structured questionnaires. We analyzed data in R version 4.0.3 (2020-10-10). We presented numerical variables as mean and standard deviation whereas categorical variables as frequency and percentage. We determined factors associated with awareness and knowledge of glaucoma using logistic regression analysis and estimated adjusted odds ratio (AOR) with 95% confidence interval. Result Of 379 participants, a total of 214 (56.5%) participants had heard about glaucoma. Out of the participants who heard about glaucoma, the mean knowledge score was 48.3±21.7 and 53.3% had good knowledge on glaucoma. The odds of having heard about glaucoma were two percent lower (AOR=0.98; 95%CI: 0.97-0.99; p-value 0.036) in the older participants compared to one year younger participant, 1.98 (95%CI:1.01-3.86; p-value 0.046) times higher among literates and 2.79 (95%CI: 1.76- 4.41; p-value < 0.001) times among participants with previous ocular examination. The odds of having good knowledge was 1.94 (95%CI: 1.10-3.42; p value 0.021) times among participants with previous ocular examinations. Conclusion The knowledge and awareness regarding glaucoma in a hospital-visiting population in central Nepal was low. Half of the participants were unaware of the disease glaucoma and half of the participants who heard of the glaucoma had poor knowledge on glaucoma.